Physician-initiated clinical study of limb ulcers treated with a functional peptide, SR-0379: from discovery to a randomized, double-blind, placebo-controlled trial - Hironori Nakagami (Nature Portfolio, 2018)
Dermatology: peptide drug development for skin ulcers Chronic leg ulcers result in substantial impairment of patient quality of life with a socioeconomic impact both in terms of medical care and missed work days. A teams led by Hironori Nakagami at Osaka University originally identified a functional peptide, SR-0379, and evaluated the safety and efficacy of SR-0379 for the treatment of leg ulcers in a physician-initiated, first-in-patient, a multi-center, double-blind, randomized clinical study. In the evaluation of efficiency, the skin ulcer reduction rates were improved for the SR-0379 treated groups in a dose-dependent manner, compared for the placebo group with no causal adverse events. Since treatment with SR-0379 for chronic leg ulcers was safe, well tolerated, and effective in this initial clinical trial, the clinical trial on next stage will be designed toward peptide drug development.